Design of Clean Water Treatment Installation and Estimation of Capex and Opex in Aek Natonang Lake, Samosir Regency - Marningot Tua Natalis Situmorang (Postgraduate, University of Mataram, 2025)
According to the national target, the community must have clean water so that planning for a clean water treatment plant that will serve the sub-district is needed. The clean water used must be in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 32/MENKES/2017 concerning Clean Water Quality Requirements. Therefore, raw water is studied in the laboratory and the results of this laboratory are the main consideration for the need for a new clean water treatment plant to improve clean water services. One of the Clean Water Treatment Plant plans is Lake Aek Natonang which is located in Tanjungan Village, Simanindo District. The processing units designed are the intake unit, pre-sedimentation unit, coagulation unit, flocculation unit, sedimentation unit, filtration unit, disinfection and reservoir. In the intake unit, it consists of a pipe carrying raw water to the pre-sedimentation unit. The coagulation unit used is hydraulic coagulation using PAC as a coagulant. The flocculation unit is designed as a hydraulic system with Polymer as a flocculant. The sedimentation unit uses a reservoir with a sedimentation zone. The disinfectant used is chlorine which is directly flowed into the reservoir unit through a pipe. Based on Capex and Opex calculations, this Clean Water Treatment Plant requires a cost of Rp. 725,635,415 and the operation of this installation requires a cost of Rp. 13,150,450/month.